MicroRNAs regulate adipocyte differentiation. (18th March 2013) - Chen, Lin; Song, Jinlin; Cui, Junhui; Hou, Jia; Zheng, Xiaohui; Li, Cai; Liu, Lei
Abstract The number of adipocytes is relevant to the extent of differentiation from pluripotent stem cells into pre‐adipocytes, whereas the size of adipocytes relates to the extent of differentiation from pre‐adipocytes into mature fat cells and the accumulation of triglyceride. Investigation of the molecular regulatory mechanism of adipocyte differentiation is not only essential for understanding the physiological processes of adipogenesis, but it is also important for identifying new biomarkers and therapeutic targets for some metabolic diseases, such as obesity and diabetes. microRNAs (miRNAs) appear to play important roles in adipocyte differentiation. During adipogenesis, miRNAs can accelerate or inhibit adipocyte differentiation by acting on transcription factors, regulating signalling pathways related to adipogenesis, or blocking the mitotic clonal expansion stage, thus regulating adipocyte development. The regulatory role of some miRNAs varies in different species or different cells. In this review, the biological characteristics of miRNA and the adipocyte differentiation process are concisely discussed. Recent advances in our understanding of the role of miRNAs in adipocytes development or adipogenesis are discussed.